Diverse Variability of Surface Chlorophyll During the Evolution of Gulf Stream Rings. Issue 5 (4th March 2021) - Ning, Jue; Chen, Ke; Gaube, Peter
Abstract: We investigate how the near‐surface chlorophyll (CHL)‐a evolves in Gulf Stream (GS) warm‐core rings (WCRs) and cold‐core rings (CCRs) using multi‐platform satellite observations. Averaged CHL anomaly (CHLA) within the rings exhibits both positive and negative linear trends during the evolution of the WCRs while negative trends dominate in CCRs. This difference is associated with a variety of physical processes occurring during the evolution process. Meanwhile, eddy‐centric analysis reveals four spatial patterns of CHLA long‐term trends, some of which highlights the importance of rings in shaping surface CHL. Short‐term fluctuations of CHLA in WCRs and CCRs are closely correlated with mixed layer depth and sea surface temperature anomaly and highlight the complex interplay between multiple mechanisms. In addition, we find higher concentration CHL in some WCRs than that in CCRs during the same season, providing an alternative view of the characteristics of the surface ecosystem in Gulf Stream rings. Plain Language Summary: The highly energetic and large‐amplitude mesoscale eddies of the Gulf Stream (GS) region, often referred to as GS rings, have significant influence on biogeochemical environment and marine ecosystem through various mechanisms. Although the importance of GS rings has been recognized, contrasting results exist regarding the role of the GS rings in the upper‐ocean ecosystem. For a better understanding of mesoscale physical and biological interactions, here we examine the temporal and spatial variability of near‐surface chlorophyll (CHL), and how it is modulated by the physical processes during individual ring's life span from satellite observations in details. Remarkable long‐term and short‐term variabilities, and different spatial patterns are found in both warm‐core rings (WCRs) and cold‐core rings (CCRs). Strikingly, the result shows that WCRs are more productive than CCRs during the decay stage, which is in contrast to the existing understanding. This study provides a comprehensive observational perspective of surface CHL variations associated with mesoscale eddies from formation to decay. Key Points: Negative trends of chlorophyll anomaly dominate in cold‐core rings (CCRs) while both positive and negative trends exist in warm‐core rings (WCRs) Short‐term fluctuations of chlorophyll anomaly are closely correlated with mixed layer depth and sea surface temperature anomaly CCRs can be distinctly less productive than WCRs in the same seasons